1994
DOI: 10.1016/s0006-3495(94)80645-9
|View full text |Cite
|
Sign up to set email alerts
|

Stereodynamic properties of the cooperative homodimeric Scapharca inaequivalvis hemoglobin studied through optical absorption spectroscopy and ligand rebinding kinetics

Abstract: The study of the thermal evolution of the Soret band in heme proteins has proved to be a useful tool to understand their stereodynamic properties; moreover, it enables one to relate protein matrix fluctuations and functional behavior when carried out in combination with kinetic experiments on carbon monoxide rebinding after flash photolysis. In this work, we report the thermal evolution of the Soret band of deoxy, carbonmonoxy, and nitric oxide derivatives of the cooperative homodimeric Scapharca inaequivalvis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
(49 reference statements)
1
35
0
Order By: Relevance
“…On the other hand, the ferrous form of the protein shows substantial stability over a wide pH range. These observations suggest that Scapharca hemoglobin has a unique heme structure that undergoes substantial redox-dependent rearrangements that stabilize the Fe-proximal histidine bond in the functional deoxy form of the protein but not in the ferric form.The homodimeric hemoglobin (HbI) 1 isolated from arcid clam Scapharca inaequivalvis possesses unique structural features (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although HbI has a low sequence homology with tetrameric mammalian hemoglobins (Hb), it has a conserved globin fold.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the ferrous form of the protein shows substantial stability over a wide pH range. These observations suggest that Scapharca hemoglobin has a unique heme structure that undergoes substantial redox-dependent rearrangements that stabilize the Fe-proximal histidine bond in the functional deoxy form of the protein but not in the ferric form.The homodimeric hemoglobin (HbI) 1 isolated from arcid clam Scapharca inaequivalvis possesses unique structural features (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although HbI has a low sequence homology with tetrameric mammalian hemoglobins (Hb), it has a conserved globin fold.…”
mentioning
confidence: 99%
“…The homodimeric hemoglobin (HbI) 1 isolated from arcid clam Scapharca inaequivalvis possesses unique structural features (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although HbI has a low sequence homology with tetrameric mammalian hemoglobins (Hb), it has a conserved globin fold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some broadening of the Soret band was observed in the presence of bare ZnO NPs. Transition from the near Gaussian to the non‐Gaussian form of the Soret band (inset of Figure ), indicated that the iron atom affected the in‐plane towards the out‐of‐heme plane and additionally produced conformational homogeneity inside the heme‐porphyrin system . The use of C ZnO = 0.0.5 mg/ml within the ZnO NP–BSA bioconjugate shown in Figure (d) gave rise to a peak at c .…”
Section: Resultsmentioning
confidence: 94%
“…The limited success of intracellular mammalian Hbs has also motivated researchers to investigate the naturally extracellular hemoglobins of invertebrates (aka Erythrocruorins or Ecs). Ecs from a variety of organisms have been studied, including annelids, mollusks, insects, snails, and many more . Overall, the most thoroughly investigated Ecs are from the annelids Lumbricus terrestris and Arenicola marina, which are both huge macromolecular complexes (MW ∼3.6 MDa).…”
Section: Introductionmentioning
confidence: 99%